1993
DOI: 10.1111/j.1651-2227.1993.tb12637.x
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment with nasal continuous positive airway pressure in very low‐birth‐weight infants

Abstract: During 1988 and 1989, a regional cohort of 81 infants with birth weights less than 1501 g were treated with oxygen only (n = 11), early continuous positive airway pressure (CPAP) (n = 68) or mechanical ventilation from birth (n = 2). We used an easily applicable lightweight CPAP system with nasal prongs and a gas jet supplemented with ventilator treatment if necessary, but with conservative criteria for ventilator treatment with tolerance of high PCO2. A total of 65 infants (80%) survived to discharge, 61 of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 18 publications
2
59
1
Order By: Relevance
“…NCPAP is effective in preventing extubation failure in preterm infants and avoiding the need for mechanical ventilation. [9][10][11][12] However, its use has been limited in some infants by common complications of CPAP devices: nasal trauma, obstruction by secretions requiring frequent removal for suctioning, kinking of the nasopharyngeal prongs in the pharynx and overall perceived patient discomfort. 13,14 Vapotherm is an HFNC system that prevents dryness of the nasal mucosa by warming and humidifying inhaled gas.…”
Section: Discussionmentioning
confidence: 99%
“…NCPAP is effective in preventing extubation failure in preterm infants and avoiding the need for mechanical ventilation. [9][10][11][12] However, its use has been limited in some infants by common complications of CPAP devices: nasal trauma, obstruction by secretions requiring frequent removal for suctioning, kinking of the nasopharyngeal prongs in the pharynx and overall perceived patient discomfort. 13,14 Vapotherm is an HFNC system that prevents dryness of the nasal mucosa by warming and humidifying inhaled gas.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 CPAP has been associated with decreased BPD in several clinical reports. [14][15][16] Multivariate regression analysis has shown intubation and mechanical ventilation of preterm infants to be the single most important predictor of subsequent BPD. 2 The controversy of early vs delayed CPAP continues as many of the trials favoring early CPAP were carried out in the larger infants prior to routine use of antenatal steroids and postnatal surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that it contributes to a reduction in the need and dependence of oxygen and respiratory rate as well as the need for mechanical ventilation [1][2].…”
Section: Introductionmentioning
confidence: 99%